Revitalizing Qienzy variant drinks MSMES in Medan Tuasan through innovation-based business models and digital transformation - Mica Siar Meiriza; Rahman Rahman; Dira Febrina Sebayang; Grace Analita Febrina Anak Ampun; Saffanah Alya Zahra; Mhd Rasyid Alfarisi; Nabila Kesya Azzahra Siregar; Ayu Primsa Br Tarigan; Listem Wisiska Situmorang; Ariel Immanuel Panjaitan; Dhiya Atikah; Siti Salwa Azalia; Nurlila Azmi Hutapea; Lasria Sitorus; Jelita Febrianti Tampubolon; Julius Kristianus Nainggolan (Universitas Nusa Cendana, 2026)
This study examines the business challenges faced by Qienzy Variant Drinks MSME in Medan Tembung and proposes revitalization strategies through innovation-driven business models and digital transformation. As micro-enterprises operate in an increasingly competitive and technology-oriented environment, the ability to innovate and adapt digitally has become essential for long-term sustainability and growth. Employing a qualitative descriptive approach, the study collected data through interviews, observations, and documentation involving the business owner as the primary informant. The findings reveal that limited product innovation, reliance on manual operational processes, inadequate utilization of digital marketing, and the absence of structured management practices have constrained the enterprise’s competitiveness and growth potential. To address these challenges, the study identifies several strategic priorities, including the adoption of digital technologies, continuous menu innovation, recruitment of personnel with relevant skills, and the implementation of a market-oriented business model. These initiatives are expected to enhance operational efficiency, strengthen market responsiveness, and improve overall business performance. The study contributes to the literature on micro-enterprise development and digital entrepreneurship by providing practical insights into how small businesses can adapt to the demands of the digital era. However, as the findings are derived from a single case study, future research is encouraged to involve a broader range of respondents or conduct comparative analyses across similar enterprises to improve the generalizability of the results. Keywords: MSME; Business Innovation ; Digital Transformation